DEVELOPMENT OF THE INSTITUTIONAL FRAMEWORK OF PUBLIC-PRIVATE PARTNERSHIP IN THE REPUBLIC OF SERBIA - Amovic, Goran (Journal of process management and new technologies, 2019)
In present-day conditions of global economy, the processes of development of national economies require the need for capital investments in the development and improvement of public infrastructure, and the provision of public services in the field of general social activities (education, health care, culture, sports) and social issues. The demand for a better infrastructure and more efficient public service, with public sector constraints, requires a new role of public sector, a new approach and new strategies. In the context of the above mentioned, Public-Private Partnership (PPP) establishes an innovative framework for more efficient implementation of public investments - faster construction, lower costs, optimal risk allocation, more efficient management, better public services, etc. In this paper we will present the most important characteristics of the Public-Private Partnership model, with a view to the chronological development of PPP institutional framework in the Republic of Serbia.